2020
DOI: 10.1186/s12870-020-2291-z
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis analysis and underlying molecular regulatory mechanism in a wide-compatible neo-tetraploid rice line with long panicles

Abstract: Background: Neo-tetraploid rice, which is a new germplasm developed from autotetraploid rice, has a powerful biological and yield potential and could be used for commercial utilization. The length of panicle, as a part of rice panicle architecture, contributes greatly to high yield. However, little information about long panicle associated with heterosis or hybrid vigor is available in neo-tetraploid rice. Results: In the present study, we developed a neo-tetraploid rice line, Huaduo 8 (H8), with long panicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 57 publications
(112 reference statements)
1
38
0
Order By: Relevance
“…The grains were labeled at the time of owering, collected 5,6,7,8,9,10,11,12,15,18,20,21, and 24 DAF and stored at -80 °C in a freezer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grains were labeled at the time of owering, collected 5,6,7,8,9,10,11,12,15,18,20,21, and 24 DAF and stored at -80 °C in a freezer.…”
Section: Methodsmentioning
confidence: 99%
“…As a basic feature in nearly all plant species, polyploidization normally results in a higher yield than that of diploid plants and is regarded as a powerful tool in crop breeding (Ramanna and Jacobsen 2003). During the last decade, the application of polyploidization has been used in rice breeding, and several highly productive hybrid rice lines have been developed (Cai et al 2007;He et al 2011;Ghaleb et al 2020). Through comparative studies between diploid and autotetraploid rice cultivars, it was shown that there are higher glutelin contents in autotetraploid cultivars than in diploid cultivars (Cai 2011).…”
Section: )mentioning
confidence: 99%
“…Knock-out of environmentally sensitive genic male sterility genes causes pollen abortion in neo-tetraploid rice Neo-tetraploid rice is a key step to overcome the sterility of F 1 hybrids in autotetraploid rice (Guo et al 2017;Bei et al 2019;Ghaleb et al 2020). To verify the up-regulation of pollen fertility gene play the important role in neo-tetraploid rice, we used CRISPR/cas9 technology to conduct the study.…”
Section: Meiosis In Neo-tetraploid Rice Compared With Its Two Parentsmentioning
confidence: 99%
“…It is great demand to reveal the mechanism of its low pollen fertility and acquired the high pollen fertility tetraploid materials. After years of efforts, we successfully developed a new "autotetraploid rice lines" by selective breeding and crossing for successive generations (Guo et al 2017;Bei et al 2019; Ghaleb et al 2020). The new "autotetraploid rice" displayed high fertility (>80%) and high heterosis while crossed with other autotetraploid rice lines having low fertility (Guo et al 2017;Chen et al 2018;Bei et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the application of polyploidization has been used in rice breeding, and several highly productive hybrid rice lines have been developed (Cai et al 2007;He et al 2011;Ghaleb et al 2020). Through comparative studies between diploid and autotetraploid rice cultivars, it was shown that there are higher glutelin contents in autotetraploid cultivars than in diploid cultivars (Cai 2011).…”
Section: Introductionmentioning
confidence: 99%